PENGEMBANGAN STANDAR ISI DAN STANDAR PROSES DALAM PENDIDIKAN GUNA MENINGKATKAN MUTU PEMBELAJARAN DI SEKOLAH - Halimatu Sakdiah; Syahrani Syahrani (Cross-border, 2022)
National Education Standards are minimum criteria regarding various relevant aspects in the implementation of the national education system and must be met by education providers or units throughout the jurisdiction of the Unitary State of the Republic of Indonesia. National Education Standards serve as the basis for planning, implementing and supervising education in the context of realizing quality national education. National Education Standards aim to ensure the quality of national education in the context of educating the nation's life and shaping the character and civilization of a dignified nation. National Education Standards are refined in a planned, directed and sustainable manner in accordance with the changing demands of local, national and global life. According to PP No. 19 of 2005, content standards are the scope of the material and the level of competence as outlined in the criteria for graduate competencies, study material competencies, subject competencies, and learning syllabus that must be met by students at certain levels and types of education. Content standards include the basic framework and curriculum structure, learning load, curriculum unit level and educational or academic calendars and in accordance with PP No. 19 of 2005 Process standards are national education standards relating to the implementation of learning in an educational unit to achieve graduate competency standards. The desired process is an interactive, inspiring, fun, challenging, motivating learning process for students to participate actively, as well as providing sufficient scope for initiative, creativity and independence according to interests and talents as well as the physical and psychological development of students.